2002
DOI: 10.1098/rstb.2001.1023
|View full text |Cite
|
Sign up to set email alerts
|

Elastin: a representative ideal protein elastomer

Abstract: During the last half century, identification of an ideal (predominantly entropic) protein elastomer was generally thought to require that the ideal protein elastomer be a random chain network. Here, we report two new sets of data and review previous data. The first set of new data utilizes atomic force microscopy to report single-chain force-extension curves for (GVGVP) 251 and (GVGIP) 260 , and provides evidence for single-chain ideal elasticity. The second class of new data provides a direct contrast betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
259
3
2

Year Published

2004
2004
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 288 publications
(277 citation statements)
references
References 49 publications
13
259
3
2
Order By: Relevance
“…In order to get single-molecule characteristic, nice curves were picked and the only last peaks that showed subsequence force dropped to zero were fitted with WLC model. The persistent length was 0.28±0.10nm, which is in a good agreement with persistent length of other proteins such as Bombyx mori silk-like [54], elastin-like [55], spider silk [52], or titin [51]. The contour length was 284±13nm which was slightly less than calculated contour length of S815K molecule (320nm).…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…In order to get single-molecule characteristic, nice curves were picked and the only last peaks that showed subsequence force dropped to zero were fitted with WLC model. The persistent length was 0.28±0.10nm, which is in a good agreement with persistent length of other proteins such as Bombyx mori silk-like [54], elastin-like [55], spider silk [52], or titin [51]. The contour length was 284±13nm which was slightly less than calculated contour length of S815K molecule (320nm).…”
Section: Resultssupporting
confidence: 80%
“…When the nonlinear profile was fitted with the WLC model, the persistence length was 0.25±0.2 nm (n=15) and the contour length was 332±161 nm (n=15). This persistence length matched well the persistence length of a elastin molecule measured from single molecule stretching experiments [60], [61], implying that the stretching behavior of SELP is mainly determined by the elastin units in SELP. The fitted contour length was comparable to its calculated contour length of 295 nm (=818 residues0.36 nm/residue), indicating that a single SELP molecule is stretched along the scan direction during this process.…”
Section: Increase In Lateral Force Originates From Stretching Laterallysupporting
confidence: 79%
“…2b). The insolubility of cross-linked elastin precludes high-resolution structural determination by techniques such as X-ray crystallography and solution nuclear magnetic resonance, and as a result the molecular structure of crosslinked elastin and hence the mechanisms which drive elastic fibre elasticity remain to be determined (Daamen et al 2007;Keeley et al 2002;Urry et al 2002). Transmission electron and atomic force microscopy (TEM and AFM) investigations, however, have revealed that the apparently amorphous elastin core is actually composed of thin rope-like filaments and globular assemblies (Ronchetti et al 1998), whilst similar features are observed by environmental SEM in coacervated recombinant human tropoelastin (Cain et al 2008) (Fig.…”
Section: Structure and Functionmentioning
confidence: 99%
“…12 This unusual transition from an unordered structure to an entropically less favored ordered conformation is caused by hydrophobic dehydration. 13,14 This means that as elastin is heated its bound water is expelled, leading to a more hydrophobic protein. 15 This results in the formation of a -spiral in which the hydrophobic side chains of the valines are interacting with each other and are shielded from the aqueous environment.…”
Section: Introductionmentioning
confidence: 99%